Multisectoral HIV/AIDS Approaches in Africa: How Are They Evolving? - Gavian, Sarah; Galaty, David; Kombe, Gilbert (International Food Policy Research Institute, 2006)
The response to HIV/AIDS in Africa has evolved considerably since the first cases were reported on the continent in the early 1980s. After the initial medical and public health responses through the mid-1990s, there was an enormous expansion in the scope of the strategic approaches and level of political and financial commitment to fight the disease. In the absence of a vaccine or cure, the global response expanded far beyond the traditional confines of the health sector. Perceiving strong links between AIDS and the greater development processes, national and international organs reached out to a wide array of stakeholders to implement a broad multisectoral agenda. This expansion in vision was accompanied by a corresponding development of institutional structures and coordination mechanisms. Efforts to extend, harmonize, and improve the management of the multisectoral response are very much continuing today.